Enhanced Raman scattering based on fabry‐perot like resonance in a metal‐cladding waveguide. (17th December 2015) - Yin, Cheng; Lu, Yan; Xu, Tian; Wei, Dan Z.; Jin, Yong L.; Fang, Jing H.; Wang, Chao N.; Huang, Mei Z.
Abstract : A liquid‐core metal‐cladding waveguide structure of millimeter scale is designed to enhance Raman signal via the excitation of Fabry–Perot‐like resonance. Theoretically, an oscillating field distribution covering the whole guiding layer is generated by the multireflection at the two metal interfaces. The large detection area covers the whole sample chamber because of the oscillating nature of excited high order modes with concentrated intensity. By adding metal nanoparticles, the Fabry–Perot‐like resonance can be combined with local surface plasmons resonance to further enhance the light‐matter interaction with the target molecules, which is also confirmed by the experimental results. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A liquid‐core metal‐cladding waveguide structure of millimeter scale is designed to enhance Raman signal via the excitation of Fabry–Perot‐like resonance. Theoretically, an oscillating field distribution covering the whole guiding layer is generated by the multi‐reflection at the two metal interfaces. The large detection area covers the sample chamber because of the oscillating nature of excited high order modes with concentrated intensity. Fabry–Perot‐like resonance can combine local surface plasmon resonance to further enhance the signals of target molecules.